Three-year follow-up of composite stent grafts used in the repair of Crawford Type III thoracoabdominal aortic aneurysms; A case report. Issue 1 (January 2020) - Tong, Yuan-hao; Yu, Tong; Zhou, Min; Liu, Chen; Li, Xiao-qiang; Liu, Chang-jian; Liu, Zhao
Complex aortic aneurysms are difficult to treat endovascularly and so techniques have been developed to broaden the management options. We report a case of 51-year-old man with several thoracoabdominal aortic aneurysms (TAAAs) who underwent endovascular repair with "off-label" stent grafts. Three aortic stent grafts and four branched stent grafts were used in the procedure using chimney and periscope techniques. The patient was followed for three years with regular computed tomography angiography (CTA). Scans at 3 and 12 months showed that the TAAAs were repaired and all visceral arteries were patent. Although, scans at the two- and three-year follow-ups showed that the stent graft in the superior mesenteric artery was occluded, the patient did not have any complications probably as a result of coeliac artery compensation.